The "Schumpeterian" and the "Keynesian" Stiglitz: Learning, coordination hurdles and growth trajectories - Giovanni Dosi; Maria Enrica Virgillito (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2016)
This work, which shall contribute to the Fest "A Just Society: Honouring Joseph Stiglitz", discusses a major unifying theme in Joe Stiglitz monumental work, namely, the analysis of economies characterised by persistent learning and coordination hurdles. In his analysis Joe is in many respects a "closet evolutionist" who in fact highlighted and explored many evolutionary properties of contemporary economies in a Schumpeterian spirit. And he went further introducing genuinely Keynesian properties e.g. coordination failures and the possibility of path-dependent multiplicity of growth trajectories which are far and beyond Schumpeterian concerns. In this short essay, we shall illustrate this point with reference to some of Stiglitz works, out of many, linking them with significantly overlapping contributions from the evolutionary camp. We group them by two major themes, namely, the consequences of learning and dynamic increasing returns, and "Keynesian" coordination failures with the ensuing possibility of multiple growth paths, fluctuations, small and big crises.
Keywords: D5; D83; E12; 330; Stiglitz; Learning; Coordination Hurdles; Growth Trajectories; Knowledge; Information